Penggunaan Model NHT Untuk Meningkatkan Hasil Belajar Matematika di SMA Alkhairat Ternate - Yani Awal (Peneliti.net, 2023)
The research objective was to determine the increase in mathematics learning outcomes through the NHT model in class X students at SMA Alkhairat Ternate. This type of research is a class action. The implementation of the research follows the stages of planning, implementing, observing and reflecting. Collecting research data using observation, student learning outcomes tests, interviews, and documentation. Researchers used quantitative analysis to calculate student learning outcomes test data and qualitative to describe the learning process and the results obtained by students in each cycle. The results showed that in cycle I, there were 17 people with a percentage of 74%, while those who had not reached the KKM were 6 people with a presentation of 26%. The average value of the first cycle is 68.26. After carrying out corrective actions, cycle II increased to 22 students who completed or achieved mastery learning with a percentage of 96.% and the remaining 1 student (4%) had not yet achieved completeness but these students also experienced changes even though they had not yet achieved completeness. Based on the list of cycle II values, it can be seen that the average student learning outcome is 78.26. Thus that the use of the NHT cooperative model can improve student learning outcomes.